Assessment of Lacrijet monocanalicular intubation for congenital nasolacrimal duct obstruction. Issue 6 (November 2022) - Hamed Azzam, Shirin; Hartstein, Morris; Dolmetsch, Angela; Mukari, Abed
Purpose: To assess the success rate and complications of Lacrijet monocanalicular stent (FCI S.A.S, Paris, France) intubation in children treated for congenital nasolacrimal duct obstruction (CNLDO). Methods: Retrospective review study which included children with CNLDO that were intubated with Lacrijet monocanalucilar silicone tube.The Lacrijet tube remained in place for 11–15 weeks post operatively and was removed in the clinic with topical anesthesia. Operative time was recorded for each case. All children were evaluated using the following parameters preoperatively and postoperatively: tear meniscus height, Fluorescein dye disappearance test (FDDT), and MUNK score. Results: The study included 20 eyes with mean age of 26.25 ± 11.25 months. 17 eyes (85%) had undergone probing previously. Mean operation time of Lacrijet intubation was 8.5 min (95% CI 7.04–9.95). Mean follow-up period was 204.65 ± 105.27 days. Lacrijet intubation resulted in statistically significant improvements in tear meniscus height ( P < .001), FDDT ( P < 0.001), and MUNK score ( P < 0.001) in all children. Two different sizes of Lacrijet intubations were used. Complete success was obtained in all cases. No complications were observed. Conclusions: Lacrijet lacrimal intubation has a high rate of success, shortens surgical time and has a low rate of complications in children with CNLDO.